Burnout In Government X And Private Y Hospital In Jambi Province - Salim, Daeng Ramadhan; Arif, Yulastri; Dorisnita, Dorisnita (Jurnal Endurance, 2018)
Background: Burnout is a matter of nursing resources that consists of emotional exhaustion, depersonalization and personal acchomplishment. The previous survey results are burnout is a Global and Indonesia issues. This study aims to determine the difference of burnout to nurses at X government hospital and private hospital Y in Jambi Province. Method: This research type is quantitative with comparative cross sectional design. The sample was taken proportionally random sampling at 190 nurses.Results: This study shows nurses in government hospitals X 48.4% experienced high emotional exhaustion, 49.5% experienced high depersonalization, 57.9% high personal acchomplishment, whereas nurses in private hospitals Y 40.0% high emotional exhaustion, 40.0% experienced high depersonalization, 36.8% personal acchomplishment. Mann Whitney U Test results showed no significant differences between emotional exhaustion and depersonalization between nurses in hospital X and Y private hospitals, but the dimensions of personal acchomplisment significant differences. Conclusions: There were no significant differences, emotional exhaution, depersonalization on nurses at X government hospitals and private Y hospitals in Jambi Province, there was a significant difference in personal acchomplishment in X goverment hospital and privateY hospital.